(Invited) Toward the Future Fuel Cell -Challenge for 2040-. (3rd July 2019) - Suzuki, Toshiyuki; Iiyama, Akihiro; Kubo, Norio; Saito, Nobuhiro; Shinohara, Kazuhiko; Shimotori, Soichiro; Sugawara, Yasushi; Yamada, Kohta
Abstract : This report considers the figure which the target value of the "NEDO 's Technology Development Roadmap for Fuel Cells and Hydrogen" is going to realize, clarified an estimate with 0.85V at 4.4A/cm 2, 1.1V at 0.2A/cm 2 in performance target required in Fuel Cell around 2040. Our estimation showed possibility that the target might be achieved within the maximum value which can be expected logically.